Pregnancy behavior in female university students. Health Service. University of Valle. March 1989 - March 1992 (Colombia Medica, 1993)
This article evaluated 162 pregnant university students who were controlled between 1.989 and 1.992 in a prenatal care program from the health service of the Universidad del Valle, Cali, Colombia. Vulvovaginosis was the most common diagnosis even though the incidence of other pathologies was lower than the general population of pregnant women in the same city. Toe frequency of toxoplasmosis was three times higher than in the USA.